Al-Tijārah wa al-Da’wah al-Islāmīyah: Dirāsah li Qaḍiyati Dukhūl al-Islām fī Indūnīsīyā - Kusmana, Kusmana (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
Among other things trade, politics, education, sufism and marriage are often deemed responsible for the spread of Islam. In the Indonesian context, however, trade is one of the most important methods. In the early period of maritime trade, the establishment of the Muslim community (ummah) and sate formation constitute the main characteristics-tightly linked to each other-of the Islamization of Nusantara. Muslims from different countries acted not only as trader but also ds propagators of Islam in some parts of Nusantara which later became centers of Islamic kingdoms.DOI: 10.15408/sdi.v7i3.704